Sistem Pengupahan Dalam Islam - Aji Damanuri (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2009)
This study aims to examine the wage system from an Islamic perspective, by highlighting the principles of justice, transparency, and humanity contained in Islamic teachings. Using a qualitative method through a literature study approach, this study analyzes primary sources such as the Qur'an, Hadith, and classical and contemporary fiqh literature. The results showed that the wage system in Islam emphasizes the importance of an agreement between workers and employers, the obligation to pay wages on time, and the prohibition of labor exploitation. Islam views wages as a right that must be fulfilled fairly as part of maintaining human dignity. This study confirms that the implementation of a wage system in accordance with Islamic values can create social justice and increase work productivity.